Pengaruh Modifikasi Media Pembelajaran Renang Terhadap Keterampilan Renang Gaya Dada - Amelia, Ayu; Gani, Ruslan Abdul; Gustiawati, Resty (Jurnal Porkes, 2025)
This study is motivated by the teacher's ability to manage the class which is lacking due to the teacher's lack of expertise in swimming, thus hindering the swimming learning process. The purpose of this study was to determine the effect of swimming learning modifications on breaststroke swimming skills in class X high school students at SMA Negeri 2 Klari School. This study used a pretest-postest group design with a quasi-experimental method. The data analysis technique used SPSS Transformation 26. This study used a population of 175 class X students followed by 2 classes totaling 35 experimental group students and 35 control group students. By using a swimming test assessment instrument. The results showed that the experimental group experienced an increase in the average score of 50.16 on the pretest to 71.88 on the posstest, the control group increased 41.25 to 66.25. the two groups were relatively balanced, namely 52.4 for the experiment and 51.7 for the control. But after the treatment, the experimental group increased significantly to 78.6, while the control group rose to 64.3. Statistical tests confirmed that this difference was significant, with a significance value of 0.048 being smaller than 0.05. In percentage terms, the use of the arm swim board & back board provided an 8.50% improvement in skills compared to the conventional method (control).